Superior ablation resistance of C/C–HfCSiC composite sharp leading edges above 2500 °C prepared by precursor infiltration and pyrolysis - Wei Li; Junshuai Lv; Jingtong Li; Lingxiang Guo; Yutai Zhang; Xiaohong Shi; Hejun Li (Journal of Materiomics)
HfCSiC-modified carbon/carbon composite (C/C–HfCSiC) sharp leading edges (SLEs) were prepared via precursor infiltration and pyrolysis for potential hypersonic applications. The effect of SiC proportion on the ablation behavior of the SLEs under oxyacetylene flames with 2.38 MW/m2 and 4.18 MW/m2 was investigated. The preferred sample with a volume ratio of HfC to SiC of 0.74 possessed almost zero degradation (linear recession rate 0.6 μm/s) up to a temperature of 2371 °C. As the temperature increases to 2527 °C in the latter condition, the SLE with less SiC (the volume ratio of HfC to SiC is 1.10) exhibited a linear recession rate of 1.03 μm/s during cyclic ablation of 3 × 40 s. Relatively more SiC addition is favorable under lower heat flux due to the better oxygen barrier performance of the scale. However, superior ablation resistance is available under higher heat flux with less SiC addition due to the higher thermal stability of the resulting oxide scale.